Influence of Tire Parameters on Contact Patch and Axle Force Generation against Short Obstacles Using DOE Approach - Vikas Birajdar; Seyed Jamaleddin Mostafavi Yazdi; Madhu Kandampadath; Mohammad Behroozi; Javad Baqersad (Vehicles)
Understanding the behavior of tires on uneven and varied road surfaces poses a substantial challenge for vehicle ride engineers. To accurately predict road load forces on the axle, various numerical ride models must be utilized to incorporate a realistic road enveloping algorithm. This algorithm filters the geometries of uneven surfaces and must be seamlessly integrated with a rigid ring model. The complexity of predicting and calculating dynamic tire response increases with varying obstacle dimensions. A two-dimensional, five-degree-of-freedom rigid ring ride model based on Short Wavelength Intermediate Frequency (SWIFT) has been developed, employing a tandem cam enveloping algorithm to filter short wavelength road obstacles. Selecting generalized cam parameters to ensure high accuracy and an enhanced runtime performance poses a challenge in specific ride simulations. A design of experiments (DOE) approach is used to identify key control factors related to the quasi-static tandem cam enveloping model and dynamic rigid ring model, which significantly affect the enveloping response. DOE findings suggest optimization strategies for selecting tire parameters to achieve a high test-to-simulation correlation with improved computational efficiency. Additionally, the study confirms the robustness of these predictions against external noise factors, including variations in tires and road conditions.